Synthesis of cyclic carbonates from diols and CO2 catalyzed by carbenes. Issue 71 (12th August 2016) - Bobbink, Felix D.; Gruszka, Weronika; Hulla, Martin; Das, Shoubhik; Dyson, Paul J.
Abstract : The synthesis of cyclic carbonates from epoxides and CO2 is a well-established reaction, whereas the synthesis of cyclic carbonates from diols and CO2 is considerably more challenging, and few efficient catalysts are available. Abstract : The synthesis of cyclic carbonates from epoxides and CO2 is a well-established reaction, whereas the synthesis of cyclic carbonates from diols and CO2 is considerably more challenging, and few efficient catalysts are available. Here, we describe heterocyclic carbene catalysts, including one derived from a cheap and efficient thiazolium salt, for this latter reaction. The reaction proceeds at atmospheric pressure in the presence of an alkyl halide and Cs2 CO3 . Reaction mechanisms for the transformations involved are also proposed.